Nondestructive Approach for Complex-Shaped Cracks in Concrete Structures by Electromagnetic Waves with FDTD Technique - Sener, Ummu S.; Eker, Sebahattin (Wiley, 2021)
Concrete cracks have no specific shape and do not show linearity. Since the natural occurrences of concrete cracks make simulation identification difficult, rectangular step function and a dynamic geometry are used to define a concrete surface crack in the natural process. A novel interior crack expression is obtained by accepting the area between two curves as a crack filled by air in concrete and modeling this area like a Riemann integral domain. Taking the partition of this integral domain, the most realistic definition of the crack is made. Electromagnetic (EM) waves are utilized for numerical simulation after identifying the defects, cracks, rebars, and geometry of concrete. Three different simulation setups with complex geometries with two different surface cracks and one internal crack are simulated using a finite-difference time-domain (FDTD) method with Gaussian pulse wave excitation. Simulations are obtained using both transverse electric (TEz) waves and transverse magnetic (TMz) waves and the results are compared with each other. Air-dried concrete specimens are molded following simulation setups with surface cracks and measurements are made nondestructively with a Vivaldi antenna array in the frequency range of 0.4–4.0 GHz. The reflection and transmission coefficients are validated by comparing the data obtained using the measurement with the results obtained from numerical simulation.